2016
DOI: 10.1152/ajpendo.00028.2015
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage infiltration into obese adipose tissues suppresses the induction of UCP1 level in mice

Abstract: Emergence of thermogenic adipocytes such as brown and beige adipocytes is critical for whole body energy metabolism. Promoting the emergence of these adipocytes, which increase energy expenditure, could be a viable strategy in treating obesity and its related diseases. However, little is known regarding the mechanisms that regulate the emergence of these adipocytes in obese adipose tissue. Here, we demonstrated that classically activated macrophages (M1 Mϕ) suppress the induction of thermogenic adipocytes in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 50 publications
9
82
1
1
Order By: Relevance
“…Recent studies have shown that β‐adrenoreceptor‐induced activation of BAT function is suppressed under chronic inflammatory conditions induced by an increase in infiltrated macrophages in obese adipose tissue . Consistent with this previous report, Dpp4 expression levels in WAT have also been shown to be elevated in obese mice .…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have shown that β‐adrenoreceptor‐induced activation of BAT function is suppressed under chronic inflammatory conditions induced by an increase in infiltrated macrophages in obese adipose tissue . Consistent with this previous report, Dpp4 expression levels in WAT have also been shown to be elevated in obese mice .…”
Section: Discussionsupporting
confidence: 87%
“…However, similar to WAT, BAT from mice fed a sufficiently sustained obesogenic diet ultimately exhibit high mRNA levels of inflammation markers, including TNFα and F4/80. . The increased levels of pro‐inflammatory cytokines in BAT depots largely reflect enhancements in the presence and activity of infiltrated pro‐inflammatory immune cells; however, such cytokines may also be secreted by brown adipocytes, which can synthetize and release TNFα and MCP‐1, amongst other cytokines .…”
Section: Inflammation In Brown Adipose Tissue and Its Metabolic Consementioning
confidence: 99%
“…Diet‐induced obesity is also associated with decreased UCP1 expression; in some cases, however, some degree of obesity‐related inflammation is seen even in the presence of increased levels of UCP1 expression and BAT thermogenesis . However, even in these experimental settings, cold‐induced thermogenesis is severely impaired in BAT from diet‐induced obese mice and in obese humans . Experimental depletion of pro‐inflammatory macrophages was shown to eliminate the suppressive effect of diet‐induced obesity on the cold‐induced up‐regulation of UCP1 .…”
Section: Brown Adipose Tissue Inflammation and Thermogenesismentioning
confidence: 99%
“…Similarly, M1 and M2 macrophages appear to have opposing actions in BAT and/or beige fat. Clodronate liposome-induced depletion of M1 macrophages increases UCP1 expression in BAT and beige fat in mice with HFD-induced obesity (266). M1 macrophages secrete a variety of proinflammatory cytokines and chemokines, including TNFα and IL1β.…”
Section: Regulation Of Brown and Beige Fat Thermogenesis By The Immunmentioning
confidence: 99%
“…IL1β directly inhibits brown adipocyte differentiation in vitro (214). TNFα suppresses expression of β3 receptors in mouse adipocytes, thus attenuating β adrenergic signaling (21), and TNFα treatment attenuates cold-induced UCP1 expression in both BAT and iWAT in C57BL mice (265). A chronic treatment with a low dose of lipopolysaccharides (LPS), which stimulate M1 polarization, impairs beige adipogenesis and induces hypothermia in C57BL mice (230).…”
Section: Regulation Of Brown and Beige Fat Thermogenesis By The Immunmentioning
confidence: 99%